Implementación de un sistema informático de análisis morfológico que permita mejorar la selección de deportistas de alto rendimiento - Zorrilla Castillo, Marjorie Cesivel. (2015)
Speaking of "sports competitions" there is a need to select the best athletes for these competitions and get good results, there are coaches who based their selection on their experience or by observing but there are many indicators that allow you to select potential sports talents including the morphological - anthropometric that it is based on the study of the size, shape, body composition, using measurements of the body, then, with the application of different methods determined some morphological variables of human structure. One of these methods is the somatotype of Heath-Carter; that “ it is a description, quantified in physical appearance, which is expressed through a numerical and graphic scale. This scale assesses three components: endomorphism, the mesomorphism and ectomorphism. This method gives several advantages on the study of sport including the determination of high-performance athletes. Due to the advantages that provides this anthropometric method and the lack of using of adequate methodologies that allow performing a selection of sports talents it was implemented a system of morphological analysis to the selection of high-performance athletes, system that allows you to compare the physical appearance of an amateur athlete with the physical appearance of an elite athlete, and on the basis of the assessment of the similarities determine whether it is a possible sporting talent and so make a selection of the best athletes for each discipline, it also allows to compare the athletes of a same sport, compare to a same athlete at various stages, to determine the tendency of sport suitable for each individual. As the Chamorro studies shows that there are significant relationships among the three components of the somatotype and other components of the human body; “endomorphism (related to adiposity), mesomorphism (osteo-muscular development) and ectomorphism (or relative linearity)”. Therefore, the system has the fractional method of Kerr that divides the body mass in mass skin, bone, fat, muscle and residual that to be compared with the results of the somatotype provides a better idea of the accuracy of the results.